2009
DOI: 10.1177/0894845308327275
|View full text |Cite
|
Sign up to set email alerts
|

Constructivist Career Development as a Paradigm of Empowerment for At-Risk Culturally Diverse College Students

Abstract: Although constructivist career theory is routinely discussed in the literature, links between theory and practice in education are lacking. The current study focused on the potential of a constructivist curriculum to empower at-risk culturally diverse college students by increasing career self-efficacy and reducing dysfunctional career thoughts. Using a pre/post-test design, 75 underprepared undergraduates who were enrolled in six sections of a constructivist career course at a large Midwestern university comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
2
29
2
1
Order By: Relevance
“…Regarding the relationship between dysfunctional career thoughts and CDSE, empirical studies (Austin & Cilliers, 2011;Grier-Reed, Appleton, Rodriguez, Ganuza, & Reschly, 2012;Grier-Reed, Skaar, & Conkel-Ziebell, 2009) have shown that the two concepts relate significantly and negatively. Grier-Reed et al (2012) discovered a negative relationship between dysfunctional career thoughts and CDSE.…”
Section: Dysfunctional Career Thoughtsmentioning
confidence: 99%
“…Regarding the relationship between dysfunctional career thoughts and CDSE, empirical studies (Austin & Cilliers, 2011;Grier-Reed, Appleton, Rodriguez, Ganuza, & Reschly, 2012;Grier-Reed, Skaar, & Conkel-Ziebell, 2009) have shown that the two concepts relate significantly and negatively. Grier-Reed et al (2012) discovered a negative relationship between dysfunctional career thoughts and CDSE.…”
Section: Dysfunctional Career Thoughtsmentioning
confidence: 99%
“…College administrators and faculty need to consider diverse theoretical and conceptual approaches when implementing career development coursework and programming (Grier-Reed et al, 2009). One study examined how career-oriented instruction employing a constructivist approach created positive outcomes for academically at-risk students representing several aspects of diversity (Grier-Reed et al, 2009).…”
Section: Career Counseling Techniques For Diverse College Studentsmentioning
confidence: 99%
“…One study examined how career-oriented instruction employing a constructivist approach created positive outcomes for academically at-risk students representing several aspects of diversity (Grier-Reed et al, 2009). Seventy-five diverse college students participated in the study, which determined that the constructivist career development approach was successful in helping this population increase their belief in their ability to make career decisions, and reduce dysfunctional thinking, specifically in terms of self-defeating thoughts, and the resulting confusion and anxiety about making career commitments (Grier-Reed et al, 2009). …”
Section: Career Counseling Techniques For Diverse College Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trata-se de examinar a prontidão de carreira em adolescentes (Usinger & Smith, 2010), delinear uma medida da prosperidade profissional (Porath et al, 2012), avaliar o grau de estresse segundo o gênero (Raghuram et al, 2012), associar traços da personalidade à escolha da especialidade médica em universitários da área (Taber et al, 2011), identificar aspirações profissionais de crianças negras (Watson et al, 2010), mensurar a eficácia de um modelo de desenvolvimento de carreira para adolescentes , comparar a visão sobre certos conceitos de carreira em crianças mais jovens e mais velhas (Howard & Walsh, 2010), determinar fatores de previsão de intenções empreendedoras em adultos (Oschonka et al, 2010) e vários outros (Ashby & Schoon, 2010;Barros & Teixeira, 2011;Blanco, 2011;Brady-Amoon & Fuertes, 2011;Braunstein-Bercovitz et al, 2012;Cha et al, 2009;Cheung & Arnold, 2010;Creed et al, 2010;Decker et al, 2012;Di Fabio & Kenny, 2012;Dipeolu et al, 2012;Domene et al;Dreyfus, 2008;Dries et al, 2012;Duffy et al, 2011;Duffy & Klingaman, 2009;Duffy & Raque-Bogdan, 2010;Emmanuelle, 2009;Faria & Saavedra, 2008;Fernandez-Arata, 2008;Forner & Dulu, 2012;Gibbons & Borders, 2010;Grier-Reed & Skaar, 2010;Grier-Reed et al, 2009;Gunkel et al, 2010;Hirschi, 2010cHirschi, , 2010dHirschi, , 2011a…”
Section: Medição Ou Previsãounclassified